Evaluation of Benzophenone-N-ethyl Morpholine Ethers as Antibacterial and Antifungal Activities. (28th January 2014) - Bushra Begum, A.; Khanum, Noor Fatima; Ranganatha, V. Lakshmi; Prashanth, T.; Al-Ghorbani, Mohammed; Khanum, Shaukath Ara
Abstract : Microorganisms are closely associated with the health and welfare of human beings. Whereas some microorganisms are beneficial, others are detrimental. Bacterial infections often produce inflammation and pains and in some instances, infections result in high mortality. Any subtle change in the drug molecule, which may not be detected by chemical methods, can be revealed by a change in the antimicrobial activity and hence microbiological assays are very useful. A series of substituted hydroxy benzophenones and benzophenone-N-ethyl morpholine ethers were screened for their antibacterial and antifungal activities. Antibacterial activity against S. aureus, E. aerogenes, M. luteus, K. pneumonia, and S. typhimurium, S. paratyphi-B and P. vulgaris bacterial strains and antifungal activity against C. albicans, B. cinerea, M. pachydermatis, C. krusei fungal strains were carried out. The bioassays indicated that most of the synthesized compounds showed potential antibacterial and antifungal agents.